MODULATING EFFECT OF NARINGENIN, A NATURAL FLAVONONE OF CITRUS FRUITS ON THE ACTIVITY OF CASPASE-1 AND PROINFLAMMATORY CYTOKINES - A BIOCHEMICAL STUDY IN RATS ADMINISTERED ETHANOL AND CERULEIN - CN, DEEPA; A, GEETHA; Antony, Fatima Cynthia (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: Citrus fruits are commonly consumed for their health benefits and contain naringenin (Nrg) as the major flavanone. The objective was to investigate the anti-inflammatory effect of Nrg by applying ethanol (EtOH) and cerulein (Cer) induced model of pancreatitis. Methods: Male albino Wistar rats were divided into four groups. Group 1 and 2 were fed normal diet. Group 3 and 4 were fed isocalorically adjusted diet containing EtOH (36% of total calories) for a total period of 5 weeks and also injected Cer intraperitoneally (20 Î¼g/kg body weight) 3 times a week from 3rd week. In addition, Group 2 and 4 rats received daily 200 mg/kg body weight of Nrg orally from 3rd week till the experimental period of 5 weeks. Spectrophotometric assay of serum lipase, amylase, oxidative stress markers, and ELISA-based determination of inflammatory markers were carried out. The results were analyzed by one-way analysis of variance with post-hoc Bonferroni test. Results: Nrg co-administration significantly decreased the levels of serum L/A ratio (18%, p=0.021), lipid peroxides, inflammatory markers interleukinâ€‘1Î² (ILâˆ’1Î²) (18%, p=0.044), IL-18 (58%, p=0.000) and caspase-1 (31.4%, p=0.000), improved antioxidant status and minimized histopathological alterations in EtOH-Cer administered rats. Conclusion: The ability of Nrg to reduce caspase-1 activity and maturation of proinflammatory cytokines could be the underlying mechanism for its anti-inflammatory action in pancreatitis. Keywords: Antioxidant, Anti-inflammatory, Interleukin-1Î², Interleukin-18, Inflammation, Pancreatitis.